Respon Fisiologis Domba Ekor Tipis dan Domba Garut Dengan Pemberian Pakan Konsentrat dan Limbah Tauge - Listya Purnamasari; Syeh Ahmad Muhammad Basalamah; Sri Rahayu; Sri Darwati (Jurnal Ilmu Peternakan Terapan, 2020)
The present study aimed to evaluate some physiological variables of thin tailed sheep and Garutsheep fed by concentrate and mung bean sprout waste diet. The physiological variables includedrectal temperature, respiration rate, and heart rate. Six Javanese thin tailed sheeps (16.27Â±0.86kg) and six Garut sheeps (10.68Â±1.82 kg) which aged less a year were selected for 4 treatments byfactorial design 2 x 2. The first factor was diet (concentrate and bean sprout waste) and the secondfactor was kind of sheep (Javanese thin tailed sheep and Garut sheep). The sheep were fedindividually for a maintenance requirement on body weight. Ambient temperature, relativehumidity, and physiological variables were measured every morning before feeding during 8weeks. The result showed that the physiological response of Javanese thin tailed sheep and Garutsheep fed by concentrate and mung bean sprout waste diet showed no interaction (P>0.05). Thephysiological response of sheep was not significantly different but the feed treatments had asignificant effect (P>0.05). Rectal temperature, heart rate, and respiration rate were still classifiedas normal so the mung bean sprout waste diet can be used as an alternative source of protein tosubstitute concentrate.